2019
DOI: 10.1128/aac.00069-19
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Acetate Potentiates the Action of Tosufloxacin against Escherichia coli Biofilm Persisters

Abstract: Formation of bacterial biofilms is a major health threat due to their high levels of tolerance to multiple antibiotics and the presence of persisters responsible for infection relapses. We previously showed that a combination of starvation and induction of SOS response in biofilm led to increased levels of persisters and biofilm tolerance to fluoroquinolones. In this study, we hypothesized that inhibition of the SOS response may be an effective strategy to target biofilms and fluoroquinolone persister cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Interestingly, the other antibiotics, such as ampicillin (Amp) and gentamicin (Gm), also showed no differences (Figure 1b). Furthermore, exposure to the SOS response inhibitor, zinc acetate (ZnAc), 37,38 slightly decreased the survival rate in the ldhA-overexpressing strain with recA, in the presence of Oflx (Figure 1c). These results suggested that recA expression is necessary for ldhA-induced persisters to survive a wide range of antibiotics.…”
Section: Reca Is Necessary For Ldha-induced Persister Formationmentioning
confidence: 99%
“…Interestingly, the other antibiotics, such as ampicillin (Amp) and gentamicin (Gm), also showed no differences (Figure 1b). Furthermore, exposure to the SOS response inhibitor, zinc acetate (ZnAc), 37,38 slightly decreased the survival rate in the ldhA-overexpressing strain with recA, in the presence of Oflx (Figure 1c). These results suggested that recA expression is necessary for ldhA-induced persisters to survive a wide range of antibiotics.…”
Section: Reca Is Necessary For Ldha-induced Persister Formationmentioning
confidence: 99%